Nature-Based Learning to Improve Emotional Regulation and Environmental Awareness in Early Childhood: A Narrative Literature Review - Nurwinda Saputri; Made Ayu Anggreni (Pt. Anagata Sembagi Education, 2026)
Early childhood is a sensitive period for the development of emotional regulation and environmental awareness, two capacities that underpin lifelong wellbeing and pro-environmental behavior. Conventional indoor, teacher-directed early childhood education (ECE) often provides limited opportunities for children to practice self-regulation through embodied, sensory-rich experience, or to develop authentic connectedness to the natural world. Nature-based learning (NBL) pedagogical approaches that situate children's play and learning in natural or naturalized outdoor settings has been proposed as a promising alternative. This article presents a narrative literature review synthesizing 25 peer-reviewed studies published between 2021 and 2026 that examine the relationship between NBL and children's emotional regulation and environmental awareness. Sources were retrieved from Scopus- and Google Scholar-indexed journals with active digital object identifiers, appraised for relevance, and thematically synthesized. Findings indicate that NBL consistently supports self-regulation, reduces externalizing behavior, and fosters nature connectedness, which in turn mediates children's environmental awareness and early stewardship behavior. Evidence further suggests that unstructured nature play, sensitive teacher scaffolding, and repeated, place-based engagement with natural elements are key mechanisms driving these outcomes. The novelty of this review lies in explicitly linking the emotion-regulation and environmental-awareness literatures through a nature-connectedness mediation pathway, an integration rarely made explicit in prior nature-based learning studies. Implications for early childhood curriculum design and teacher practice are discussed.